Boron Element Nanowires Electrode for Supercapacitors. Issue 20 (25th March 2018) - Xue, Qi; Gan, Haibo; Huang, Yan; Zhu, Minshen; Pei, Zengxia; Li, Hongfei; Deng, Shaozhi; Liu, Fei; Zhi, Chunyi
Abstract: The pursuit of new categories of active materials as electrodes of supercapacitors remains a great challenge. Herein, for the first time, elemental boron as a superior electrode material of supercapacitors is reported, which exhibits significantly high capacitances and excellent rate performance in all alkaline, neutral, and acidic electrolytes. Notably, boron nanowire‐carbon fiber cloth (BNWs‐CFC) electrodes achieve a capacitance up to 42.8 mF cm −2 at a scan rate of 5 mV s −1 and 60.2 mF cm −2 at a current density of 0.2 mA cm −2 in the acidic electrolyte. Moreover, in all these three kinds of electrolytes, BNWs‐CFC electrodes demonstrate a decent cycling stability with >80% capacitance retention after 8000 charging/discharging cycles. The Dominating energy storage mechanism of BNWs in the different electrolytes is analyzed by looking into the kinetics of the electrochemical process. Subsequently, the BNWs‐CFC electrode is used to fabricate a flexible solid‐state supercapacitor, which reveals a specific capacitance up to 22.73 mF cm −2 and good mechanical performance after 1000 bending cycles. This study opens a new avenue to explore elemental boron‐based new nanomaterials for the application of energy storage with superior electrochemical performance. Abstract : Boron element nanowires as electrodes of supercapacitors are reported for the first time, exhibiting remarkable capacitances up to 60.2 mF cm −2 at 0.2 mA cm −2 and good cycling performance in all alkaline, neutral, and acidic electrolytes. Moreover, the application of boron nanowire‐carbon fiber cloth for flexible all‐solid‐state supercapacitor is demonstrated which reveals good mechanical performance even after 1000 bending cycles.